Estimating erosion control performance of soil management practices in Douro viticulture - Figueiredo, Tomás de (2020)
Conventional soil management (sm) in Douro viticulture, Portugal, comprise several weed control tillage operations along the crop cycle. Alternative sm practices reduce or exclude tillage, keeping ground cover for large part of the wetter seasons. Aiming at comparing the relative performance in erosion control of alternative sm practices, this study used long term records from a Douro vineyard as vine and ground vegetation evolution, crop management operations and detailed rainfall data. The USLE C factor was calculated combining vine row cover and inter-row ground cover effects in the typical vine cycle. With rainfall erosivity temporal distribution, erosion control by ground vegetation management options, representing different sm practices, was assessed for conventional and alternative (imposing different ground vegetation density, removal date and residues level after weed control). Results compare relative soil protection performance of alternative sm practices with conventional sm. Leaving residues over ground after weed control works better (54% increase in erosion control for 80% residue cover), than delaying weed control date (37% increase for a delay to mid-July), while increasing sown ground vegetation density is not so effective (17% increase for 80% cover). The methodological approach and results of this study are expected to contribute to better adjust sm practices for erosion control in Douro viticulture.